Variation of Nicotine Metabolism in Adult Men in the Jakarta Clinical Laboratory - R. Mustarichie (Journal of Global Pharma Technology, 2016)
Objective: Nicotine, a mayor addictive constituent of tobacco plays a critical role in smoking addiction. Nicotine is primarily metabolized to cotinine. The objective of the research was to determine the variation of Nicotine metabolism in adult men in the Jakarta Clinical Laboratory. Methods: The research was done to 27 men aged 19-45 years old, which consisted of 6 smokers and 21 nonsmokers. Nicotine and cotinine of the plasma concentration 2 hours after chewing one piece of nicotine gum were determined by Liquid Chromatography-Mass Spectrometry (LC-MS) method. Results: The cotinine/nicotine ratio of the plasma concentration was calculated as an index of nicotine metabolism. Scatter plot cotinine/nicotine ratio of showed distribution heterogeneous (not homogeneous).Conclusion: It could be concluded that variation nicotine metabolism could be categorized to light nicotine metabolism (<0, 22), medium (0, 22 - 4, 19), and heavy (> 4, 19).Keyword: Nicotine metabolism, Cotinine/nicotine ratio.